Present Status and Future Exploitation Strategies for Tuna Fishing in Indian EEZ - V., Vijayan (Fishery Technology, 2025)
Tuna and tuna like fishery resources are underexploited in coastal waters as well as in Indian EEZ. Fishing regulations in certain areas and inadequacy of suitable gear to be employed in a significant and dedicated manner are cited as reasons for the present situation. This communication traces the present status of the fishery, the gear employed at present, the fishing season, the future fishing effort and strategies for optimum exploitation of this valuable stock which at present is exploited to the level of only 1.7% of the available coastal resources, leaving the oceanic stock totally unexploited.